Contact tracing: Achieving equilibrium between blockchain solutions and privacy amid the novel coronavirus pandemic. Issue 2 (4th October 2022) - Moraes, Trícia Karla Lacerda; Cernev, Adrian Kemmer; Diniz, Eduardo Henrique
In moments of scepticism and hopelessness, the drive to satisfy collective needs pushes humanity to accomplish incredible feats to ensure our survival on earth. Indeed, the current global crisis caused by the novel coronavirus is no exception. We are struggling with the abrupt spread of this illness and continuously striving to find efficient solutions. This has been André Salem Alégo's primary inspiration since the crisis hit his country in March 2020. He is the chief executive officer of Blockforce, a blockchain-based SocialTech. Having observed the effects of novel coronavirus, André examined various approaches that could help contain the spread of the virus and keep society safe. He came up with the idea for an innovative service called Desviralize, which supports pandemic crisis monitoring through contact-tracing with the use of blockchain technology. This teaching case covers how an emergent technology evolves amid the pandemic. It draws attention to important facts related to the digital era such as data security and privacy in the context of Desviralize and Blockforce's chief executive officer's strategies for boosting platform growth within the constraints imposed by data protection regulation, the critical pandemic situation, and the ethical aspects of the application of technology.